Asparaginyl endopeptidase protects against podocyte injury in diabetic nephropathy through cleaving cofilin-1 - Lei, Chuntao; Li, Mengran; Qiu, Yang; Xie, Yaru; Hao, Zhe; Yin, Xingjie; Zhang, Zhentao; Su, Hua; Yang, Linlin; Lin, Jihong; Hammes, Hans-Peter; Zhang, Chun (Cell death & disease, 2022)
Podocyte injury and loss are critical events in diabetic nephropathy (DN); however, the underlying molecular mechanisms remain unclear. Here, we demonstrate that asparaginyl endopeptidase (AEP) protects against podocyte injury through modulating the dynamics of the cytoskeleton. AEP was highly upregulated in diabetic glomeruli and hyperglycemic stimuli treated-podocytes; however, AEP gene knockout and its compound inhibitor treatment accelerated DN in streptozotocin-induced diabetic mice, whereas specific induction of AEP in glomerular cells attenuated podocyte injury and renal function deterioration. In vitro, elevated AEP was involved in actin cytoskeleton maintenance and anti-apoptosis effects. Mechanistically, we found that AEP directly cleaved the actin-binding protein cofilin-1 after the asparagine 138 (N138) site. The protein levels of endogenous cofilin-1 1-138 fragments were upregulated in diabetic podocytes, consistent with the changes in AEP levels. Importantly, we found that cofilin-1 1-138 fragments were remarkably unphosphorylated than full-length cofilin-1, indicating the enhanced cytoskeleton maintenance activity of cofilin-1 1-138. Then we validated cofilin-1 1-138 could rescue podocytes from cytoskeleton disarrangement and injury in diabetic conditions. Taken together, our data suggest a protective role of elevated AEP in podocyte injury during DN progression through cleaving cofilin-1 to maintain podocyte cytoskeleton dynamics and defend damage.